100 GHz pulse waveform measurement based on electro-optic sampling. (11th April 2018) - Feng, Zhigang; Zhao, Kejia; Yang, Zhijun; Miao, Jingyuan; Chen, He
Abstract: We present an ultrafast pulse waveform measurement system based on an electro-optic sampling technique at 1560 nm and prepare LiTaO3 -based electro-optic modulators with a coplanar waveguide structure. The transmission and reflection characteristics of electrical pulses on a coplanar waveguide terminated with an open circuit and a resistor are investigated by analyzing the corresponding time-domain pulse waveforms. We measure the output electrical pulse waveform of a 100 GHz photodiode and the obtained rise times of the impulse and step responses are 2.5 and 3.4 ps, respectively.